FIFA Land 2006TM: Alliances between Security Politics and Business Interests for Germany's City Network - Klauser, Francisco (Barcelona: CCCB, 2008)
The purpose of this paper is to point out through which actions and strategies and to which consequences, security governance at the FIFA World Cup 2006 in Germany imposed its logic on urban space. In this, the World Cup is both understood as a key moment of ‘urban entrepreneurialism’ and as a powerful illustration of the deep connection between security politics, economic interests and space.